Research on the Remedy Mechanism of Lawyer’s Right to Defense - Ruolin Tan (Law and Economy, 2022)
Through analyzing the current lawyer’s defense right, this paper finds some problems such as the lack of guarantee for the exercise of lawyer’s right to meet the suspect and lawyer’s right to consult the case materials, the lack of guarantee for lawyer’s right to gather evidence, and the lack of guarantee for lawyer’s defense right at trial, etc. To solve the above problems, first, this paper analyzes the existing remedy mechanism for lawyer’s right to defense through three aspects: the complaint remedy mechanism, the accusation and petition remedy mechanism, and the appellate remedy mechanism, respectively. Then, the paper puts forward the suggestions to improve the remedy mechanism of the lawyer’s right to defense: first, establishing the judicial remedy mechanism of lawyer’s right to defense in the pre-trial procpretrialcond, improving the judicial remedy mechanism of lawyer’s right to defense at trial, and third enhancing the legal force of lawyer’s right to defense.